2021
DOI: 10.1111/jan.14814
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐methods systematic review: Cultural attitudes, beliefs and practices of internationally educated nurses towards end‐of‐life care in the context of cancer

Abstract: Aim To identify and analyse the cultural attitudes, beliefs and practices of internationally educated nurses towards end‐of‐life care in the context of cancer. Background Cultural heritage shape beliefs and practices about cancer and end of life, which complicates nursing care delivery. While previous studies centred on diverse patients’ perspectives and cultural competence of healthcare professionals, little analysis available focusing on the cultural attitudes and beliefs of care providers from diverse backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This religious factor may explain why there were differences in nurses' responses about their belief in their ability to preserve patients' dignity until the moment of death (Xiao et al, 2021 ). A systematic review by Balante et al ( 2021 ) confirmed that faith and religion often guide end‐of‐life approaches. Their findings indicated that RNs consider their faith as an integral part of their professional role when providing end‐of‐life care, and they felt satisfied that their faith guided them in their decisions to support patients and their families (Balante et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This religious factor may explain why there were differences in nurses' responses about their belief in their ability to preserve patients' dignity until the moment of death (Xiao et al, 2021 ). A systematic review by Balante et al ( 2021 ) confirmed that faith and religion often guide end‐of‐life approaches. Their findings indicated that RNs consider their faith as an integral part of their professional role when providing end‐of‐life care, and they felt satisfied that their faith guided them in their decisions to support patients and their families (Balante et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a situation is a very good opportunity for students to learn about end-of-life care. Balante J et al thinks stakeholders, such as the nursing workforce, need to play an active role in providing a culturally inclusive workplace to encourage students to experience end-of-life care [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chen et al (2017) also indicated that the time to acquire the necessary knowledge and skills and provide culturally competent care was a significant barrier. In the studies we reviewed, a lack of knowledge of the patient's culture resulted in discomfort for both nurses and patients (Balante et al, 2021;Shepherd et al, 2019). Wesołowska et al (2018) suggested that these problems could be solved by developing cultural competencies.…”
Section: Discussionmentioning
confidence: 99%